2018
DOI: 10.1186/s12991-018-0178-2
|View full text |Cite
|
Sign up to set email alerts
|

A survey of caregiver burden in those providing informal care for patients with schizophrenia or bipolar disorder with agitation: results from a European study

Abstract: BackgroundAgitation is a common feature of bipolar disorder and schizophrenia. Previous research indicates that specific symptoms impact caregiver burden in these conditions, but the impact of agitation on caregiver experience is poorly understood. The aim of this study was to characterise caregiver burden in providers of informal care for patients with bipolar disorder and schizophrenia who experience agitation.MethodsIn total, 297 matched patient and caregiver surveys were collected across the UK, Germany an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
0
26
0
3
Order By: Relevance
“…In contrast to the duration of caregiving, the role of hours spent on caregiving per week or month showed mixed results. De Almeida Mello et al's [48] and Blanthorn et al's [52] cross-sectional research and Lethin et al's [45] and Guerriere et al's [44] longitudinal studies considered hours spent on caregiving a determinant of caregiver burden. However, Riffin et al's cross-sectional study [51] reported that time spent is no longer associated with caregiver burden after accounting for the number of caregiving tasks.…”
Section: General Stressorsmentioning
confidence: 99%
“…In contrast to the duration of caregiving, the role of hours spent on caregiving per week or month showed mixed results. De Almeida Mello et al's [48] and Blanthorn et al's [52] cross-sectional research and Lethin et al's [45] and Guerriere et al's [44] longitudinal studies considered hours spent on caregiving a determinant of caregiver burden. However, Riffin et al's cross-sectional study [51] reported that time spent is no longer associated with caregiver burden after accounting for the number of caregiving tasks.…”
Section: General Stressorsmentioning
confidence: 99%
“…Patients experience initial symptoms and escalate unpredictably to a more severe level of agitation in outpatient settings such as their homes or workplaces, where early and rapid symptom relief is needed to avoid the need for emergency room attendance or psychiatric hospitalisation. Indeed, agitation places a considerable burden both on community-dwelling patients and their caregivers as has been discussed [ 51 , 52 ].…”
Section: Managing Agitation In Community-dwelling Patients With Schizmentioning
confidence: 99%
“…Alongside the patient-focused survey described above, a survey of caregivers was also conducted [ 51 ]. A total of 297 caregivers of patients who took part in the patient survey completed the caregiver survey.…”
Section: Managing Agitation In Community-dwelling Patients With Schizmentioning
confidence: 99%
“…Patients with bipolar disorder tend to experience mild to severe restlessness and irritation. Caregivers are reported to have a great role in recognizing, intervening, and supervising in taking medication during these episodes [11].…”
Section: Severity Across the Globementioning
confidence: 99%
“…They are in most cases the partner, spouse or parent of the patient. In a survey conducted in 2016, amongst caregivers of bipolar disorder, it was reported that 49% of the caregivers had to make changes in their employment status because of the patients [11]. The level of distress was noted to be higher in females [17], with 72% of the total caregivers being females [11].…”
Section: Caregivers Burdenmentioning
confidence: 99%